Old boys' network in general practitioner's referral behavior - Franz Hackl; Michael Hummer; Gerald Pruckner (Johannes Kepler University of Linz, Department of Economics, 2013)
We analyzed the impact of social networks on general practitioners' (GPs) referral behavior based on administrative panel data from 2,684,273 referrals to resident specialists made between 1998 and 2007. To construct estimated social networks, we used information on the doctors' place and time of study and their hospital work history. We found that GPs referred more patients to specialists within their social networks and that patients referred within a social network had fewer follow-up consultations and were healthier as measured by the number of inpatient days. Consequently, referrals within social networks tended to decrease healthcare costs by overcoming information asymmetry with respect to specialists' abilities. This is supported by evidence suggesting that within a social network, better specialists receive more referrals than worse specialists in the same network.
Keywords: I1; I11; 330; Referral behavior; general practitioners; information asymmetry; social networks; Ärzte; Soziales Netzwerk; Krankenhaus; Österreich